Ctr-1 Mets7 motif inspiring new peptide ligands for Cu(i)-catalyzed asymmetric Henry reactions under green conditions. Issue 75 (27th July 2016) - Pellegrino, Sara; Facchetti, Giorgio; Contini, Alessandro; Gelmi, Maria Luisa; Erba, Emanuela; Gandolfi, Raffaella; Rimoldi, Isabella
Abstract : Hybrid catalysts were developed from the Cu(i ) binding domain of Ctr1 protein and their activity was evaluated in an asymmetric Henry reaction. Abstract : Taking inspiration from the Ctr-1 Mets7 Cu(i ) binding motif, effective hybrid catalysts have been developed for asymmetric Henry condensations under green conditions. The introduction of an unnatural dipeptide mimic allowed to increase the catalytic performance. Metal transporters' binding domains could be exploited as a strategy for designing hybrid catalysts for homogeneous catalysis.